Transient fatigue is not influenced by ball-in-play time during elite rugby league matches - Waldron, M.; Thomson, E.; Highton, J.; Twist, C. (The Journal of Strength and Conditioning Research, 2019)
The capacity to sustain high-speed running is important for rugby league players. Transient fatigue, described as a reduction in high-speed running in the 5 minutes after a peak 5-minute period, is a phenomenon observed during rugby league matches. This concept has recently been questioned based on the proposed confounding influence of ball-in-play time during these periods. Therefore, this study examined the changes in high-speed running (>14 km/h) of elite rugby league players, and ball-in-play time, during the peak, subsequent, and mean 5-minute periods of 5 competitive matches using 5-Hz Global Positioning System devices. The suitability of ball-in-play time as a covariate was also evaluated. The high-speed running and ball-in-play time was different between peak (26.7 ± 5.5 m/min and 177 ± 37 seconds) and subsequent (12.1 ± 6.2 m/min and 147 ± 37 seconds) 5-minute periods (p = 0.05; most likely <). However, there was no relationship (r = 0.01 to -0.13; p > 0.05) between ball-in-play time and high-speed running, and ball-in-play time was not independent of the match period. This study has reaffirmed the presence of transient fatigue during elite rugby league matches but questioned the influence of ball-in-play time as a confounding factor. These observations have implications for the design of appropriate training practices and informing tactical strategies used by coaches. Most importantly, any practitioner wishing to measure transient fatigue could follow a similar statistical approach taken herein and based on the current findings would not need to account for ball-in-play time as a confounding variable.